2019
DOI: 10.7322/jhgd.157749
|View full text |Cite
|
Sign up to set email alerts
|

Mapa da vulnerabilidade social do município de Natal-RN em nível de setor censitário

Abstract: Introduction:The concept of vulnerability describes the coexistence, cumulativeness or spatial superposition of poverty, social deprivation and exposure to situations of environmental risk, where there is exposure to risk, incapacity of reaction and difficulty in adapting in the face of risk materialisation.Objective: Evaluate the spatial distribution of Social Vulnerability Risk at a census sector level for the municipality of Natal, Northeast Brazil. Methods:Ecological study that utilised the 895 census sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
3
Order By: Relevance
“…Recent studies that measured social vulnerability in the municipality of Natal showed that the most vulnerable areas of the city are located in the suburbs, notably in the western and northern administrative zones, in a pattern similar to that observed with the HII 42,43 . Understanding the occupation of urban space in cities helps to explain socio-spatial segregation, which will ultimately have an impact on health.…”
Section: Resultsmentioning
confidence: 52%
“…Recent studies that measured social vulnerability in the municipality of Natal showed that the most vulnerable areas of the city are located in the suburbs, notably in the western and northern administrative zones, in a pattern similar to that observed with the HII 42,43 . Understanding the occupation of urban space in cities helps to explain socio-spatial segregation, which will ultimately have an impact on health.…”
Section: Resultsmentioning
confidence: 52%
“…presents social vulnerability in some areas, mainly related to the financial situation 14 . In 2015, Santa Cruz had 38,538 thousand inhabitants and eight municipal schools in the urban area.…”
Section: Resultsmentioning
confidence: 99%
“…Al considerarse la distribución espacial del IVS, se constató que aquellos ubicados en la periferia presentaron niveles más elevados de vulnerabilidad social, lo que corrobora con otro estudio realizado en Brasil (16) . Considerando los principios del Sistema Único de Salud, la reducción de la desigualdad social debe contemplar la garantía de acceso a los servicios de salud y a recursos de protección social a poblaciones más vulnerables.…”
Section: Discussionunclassified